PENGEMBANGAN E-MODUL BERBASIS PMRI PADA MATERI GARIS DAN SUDUT - Sumandani, Arin Meimatul; Saraswati, Sari (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2022)
Understanding of mathematical concepts is very important for students, especially in material lines and angles. In the subject of lines and angles, many students have not mastered the concept well, so many students experience difficulties. The purpose of this study is to produce an e-module based on Indonesian Realistic Mathematics Education (PMRI) on line and angle material that is valid, practical, and effective. This study employed the ADDIE model development research procedure which consisting 5 stages: analysis, design, development, implementation, and evaluation. The product of this research is an e-module based on PMRI on line and angle material. The results showed that the developed e-module achieved the criteria of being valid, practical and effective The results of the development show that the e-module is included in the valid criteria with an average score percentage of 89%, practical with an average score percentage of 97.25% and effective with an average score percentage of 76.31%. The developed e-module is effective in teaching the concept of lines and angles for class VII. Keywords: mathematics, e-module, development, RME. Â